ANALISIS BIAYA OPERASIONALKENDARAAN ANGKUTAN BBM PADA PT ARTO LANGGENG REJEKI - Yahya Nusa (Unit Pengelola dan Pengembangan Jurnal Ilmiah dan Informasi (UPPJII) STIE Jambatan Bulan, 2018)
The aim to be achieved in this research is to know the amount of vehicle operating costs (VOC) was spended by PT Arto Langgeng Rejeki to deliver the fuel. There are several techniques of data analysis used to know the vehicle operating costs at PT Arto Langgeng Sejati are as follows: 1) To calculate the cost of fuel consumption at PT Arto Langgeng Rejeki used the formula: BBBM = KBBMx HBBM; 2) To calculate the cost of oil consumption at PT Arto Langgeng Rejeki used the formula: BO = KOx HO; 3) To calculate the cost of spare parts consumption at PT Arto Langgeng Rejeki used the formula: BP = P x HKB; 4) To calculate the cost of tire consumption at PT Arto Langgeng Rejeki used the formula: B = KB x HB / 1000; 5) To calculate the wage of maintenance workers at PT Arto Langgeng Rejeki used the formula: BU = JP x UTP / 1000. The results of research showed that: 1) The cost of consumption of fuel oil (BBM) on PT Arto Langgeng Rejeki used in the operation of the one unit tank car with capacity for 5.000 liters of Rp 4.127.200; 2) The cost of oil consumption at PT Arto Langgeng Rejeki used in the operation of the one unit tank car with capacity of 5.000 liters of Rp 2.000.000; 3) The cost of spare parts consumption at PT Arto Langgeng Rejeki used in the operation of the one tank car with capacity of 5.000 liters Rp 350.000.000; 4) The cost of tire consumption at PT Arto Langgeng Rejeki used in the operation of hte one unit tank car with capacity of 5.000 liters of Rp 16,500,000; 5) The cost of maitenance workers at PT Arto Langgeng Rejeki to be done to suport operation one unit tank car with capacity 5.000 liter of Rp 2,240,000.